2013
DOI: 10.1002/jor.22360
|View full text |Cite
|
Sign up to set email alerts
|

Effect of platelet-rich plasma on the biologic activity of the human rotator-cuff fibroblasts: A controlled in vitro study

Abstract: To assess the in vitro effect of platelet-rich plasma (PRP) on biological activity of the human rotator cuff fibroblasts and to describe the optimal dose-response to maximize cellular stimulation while reducing potential risk. Rotator cuff (RC) fibroblasts of n ¼ 6 patients (mean age of 65.2 years) undergoing arthroscopic cuff tear reconstruction were cultured in vitro for 21 days and stimulated with PRP in three different concentrations (1-, 5-, and 10-fold). Samples were obtained for DNA and GAG measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 28 publications
6
42
0
Order By: Relevance
“…Sadoghi et al treated human tenocytes with PRP of varying platelet concentrations (1-, 5-, and 10-fold). All PRP treatments increased proliferation, DNA levels, and GAG levels, although lower concentrations were more effective [74]. Jo et al found that PRP significantly increased the production of matrix, GAGs, and Col-1 and III in human tenocytes in a dose-dependant manner [75].…”
Section: Platelet-rich Plasmamentioning
confidence: 99%
“…Sadoghi et al treated human tenocytes with PRP of varying platelet concentrations (1-, 5-, and 10-fold). All PRP treatments increased proliferation, DNA levels, and GAG levels, although lower concentrations were more effective [74]. Jo et al found that PRP significantly increased the production of matrix, GAGs, and Col-1 and III in human tenocytes in a dose-dependant manner [75].…”
Section: Platelet-rich Plasmamentioning
confidence: 99%
“…Recent studies [58,59,110,114,137] and metaanalyses described no consistent effect on re-tear rates or at least uncertainty about the evidence [17,119]. Possible explanations for these contradicting findings are that stimulating effects of PRP may turn into the opposite beyond an ideal dosage [13].…”
Section: Rotator Cuff Repair and Growth Factors: Are We Really Doing mentioning
confidence: 99%
“…Limitations of this study include the possibility that the measured force that caused failure of the un-operated tendons may have been underestimated due to the design of the mechanical testing apparatus [27]. Sadoghi et al [28] studied whether rotator cuff fibroblasts isolated from human subjects would have dosedependent increased proliferation when exposed to PRP. They showed that a concentration of platelets five times that of plasma had an effect on increasing human rotator cuff fibroblast proliferation, specifically, increasing the DNA to glycosaminoglycan ratio (the latter being one of the markers for tendon degeneration).…”
Section: Basic Sciencementioning
confidence: 99%